Old Mikamba had a farm - Isadora, Rachel (Nancy Paulsen Books, an imprint of Penguin Group (USA) Inc., 2013)
The inhabitants of Old Makimba's farm in Africa, including a baboon, an elephant, and a lion, are described, verse by verse. Includes facts about African animals.